2012
DOI: 10.1111/j.1365-2133.2012.10856.x
|View full text |Cite
|
Sign up to set email alerts
|

Hair follicle stem cell differentiation is inhibited through cross‐talk between Wnt/β‐catenin and androgen signalling in dermal papilla cells from patients with androgenetic alopecia

Abstract: These results suggest that androgens deregulate DPC-secreted factors involved in normal HF stem cell differentiation via the inhibition of the canonical Wnt signalling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 36 publications
3
105
0
2
Order By: Relevance
“…Several studies have suggested a relationship between β -catenin signaling and alopecia. When androgen treated DPC in androgenic alopecia patients, β -catenin was significantly decreased in the cytoplasm, while GSK-3 β was increased [36, 37]. BIO (GSK-3 β inhibitor) enhances hair-inducing ability through stabilization of β -catenin and elevated the alkaline phosphatase and insulin-growth factor-1 gene expressions [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested a relationship between β -catenin signaling and alopecia. When androgen treated DPC in androgenic alopecia patients, β -catenin was significantly decreased in the cytoplasm, while GSK-3 β was increased [36, 37]. BIO (GSK-3 β inhibitor) enhances hair-inducing ability through stabilization of β -catenin and elevated the alkaline phosphatase and insulin-growth factor-1 gene expressions [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…The HF-enriched primary cultures (HFSCs) were obtained as previously described [34]. In brief, skin samples were incubated in 1 mg/ml collagenase/dispase (Sigma-Aldrich) overnight at 4°C, and telogen follicles were pulled out and incubated in 0.05% trypsin-0.23 mM EDTA (Gibco, Invitrogen, Life Technologies).…”
Section: Cell Culturesmentioning
confidence: 99%
“…The follicular dermal papilla cells can induce hair formation in rodents once they are located near the epithelium [31,32] or generate hair follicle neogenesis in vivo when combined with hair follicle stem cells [33]. The DPCs are also able to induce the differentiation of bulge stem cells into hair-lineage cell types in vitro [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the hairs regrow after the chemotherapy treatment is finished. In contrast, androgens inhibit Wnt signaling [48], which is required for the ability of the DP to induce hair cycling and regeneration [49]. This mechanism implies that targeting androgens as a therapy for AGA gives only a transient effect, while CIA can completely recover and hair growth becomes normal again.…”
Section: Androgenic Alopeciamentioning
confidence: 99%